2017
DOI: 10.1080/09540121.2017.1363362
|View full text |Cite
|
Sign up to set email alerts
|

Engaging HIV-positive clients in care: acceptability and mechanisms of action of a peer navigation program in South Africa

Abstract: Antiretroviral therapy (ART) could curtail the HIV epidemic, but its impact is diminished by low uptake. We developed a peer navigation program to enhance engagement in HIV care, ART adherence, and behavioral prevention. In preparation for a randomized controlled trial, the program was piloted over four months at two primary health clinics in South Africa's North West Province. Newly diagnosed, HIV-positive clients met regularly with navigators to address barriers to care, adherence, and prevention. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
(37 reference statements)
5
33
0
Order By: Relevance
“…6,9 Counseling patients to replace adherence-impeding stigma–medication management strategies with alternative medication routines that address stigma concerns may be implemented by lay counselors. 37…”
Section: Discussionmentioning
confidence: 99%
“…6,9 Counseling patients to replace adherence-impeding stigma–medication management strategies with alternative medication routines that address stigma concerns may be implemented by lay counselors. 37…”
Section: Discussionmentioning
confidence: 99%
“…Interventions targeting this mechanism may provide a pathway toward training peers or partners to support PLWH in nonjudgmental and nonconfrontational ways (e.g. using motivational interviewing techniques), and may ultimately be effective in helping PLWH to initiate and stay on ART, as has been previously suggested [57,58].…”
Section: Discussionmentioning
confidence: 98%
“…76 Navigation may also be beneficial for patients with diagnoses that are socially stigmatized and where stigma represents a barrier to care. 77 For example, participants in a peer navigation program for patients who were HIV-positive reported that navigators were an important source of support, particularly in addressing psychological barriers, such as fear and shame, and for those who had not disclosed their diagnosis. 77,78 Navigation programs have also been associated with increased service use, including linkages to care, adherence to recommended testing and treatment, and timeliness in obtaining health care services, even for patients who are at high risk for delays in care.…”
Section: Navigation Outcomes Researchmentioning
confidence: 99%
“…77 For example, participants in a peer navigation program for patients who were HIV-positive reported that navigators were an important source of support, particularly in addressing psychological barriers, such as fear and shame, and for those who had not disclosed their diagnosis. 77,78 Navigation programs have also been associated with increased service use, including linkages to care, adherence to recommended testing and treatment, and timeliness in obtaining health care services, even for patients who are at high risk for delays in care. 44,45,64,[79][80][81] In a meta-analysis of randomized controlled trials (RCTs) of navigation to improve health care use (most were focused on adult patients with cancer), pooled analysis revealed that navigation increased the likelihood of health screening uptake by 2.5 times and attendance at recommended appointments by almost 3 times.…”
Section: Navigation Outcomes Researchmentioning
confidence: 99%